Do Supplementary Sales Forecasts Increase the Credibility of Financial Analysts’ Earnings Forecasts? - Keung, Edmund C. (The Accounting Review, 2010)
ABSTRACT: This study examines whether the market reacts more strongly to earnings forecast revisions when financial analysts supplement their earnings forecasts with sales forecasts. I find that earnings forecast revisions supplemented with sales forecast revisions have a greater impact on security prices than do stand-alone earnings forecast revisions, controlling for the incremental information content in sales forecasts. Supplemented earnings forecasts are more accurate ex post, controlling for other individual analyst characteristics. Results are robust to controlling for earnings persistence and time effects. Taken as a whole, financial analysts are more likely to supplement their earnings forecasts with sales forecasts when they have better information. Supplementary sales forecasts appear to lend credibility to earnings forecasts because financial analysts provide sales forecasts when they are more informed.